Implementation of Rainwater Harvesting System in Development Project Among Local Authorities in Malaysia - MOHD YUSRI, NURUL FAKHIRA; AHMAD NAZRI, MOHD ARIFF (Recent Trends in Civil Engineering and Built Environment, 2022)
Rainwater harvesting system (RHS) is an emerging technology in the world. Several studies have shown that rainwater harvesting system indicates many benefits to environment societies, government and others. However, RHS is still new in Malaysia and the adoption is still at an early stage. The purpose of this study was to determine the characteristics of RHS implementation among local authorities in Malaysia and summarize the standard and guidelines for RHS in any development project in Malaysia. The study method by used are by a research approach and systematic review. Both implementations method will be focussing in achieve the objective of this study. Therefore, the data collected will be referred the objectives of this study and result of the data analysis will be as an orientation for development RHS in Malaysia.10 local authorities in Malaysia had been selected for this study purpose. It can conclude that each local authority had their own guidelines in implementation RHS in Malaysia. All those guidelines had been discovered that can give impact to the future trends of implementation of RHS in Malaysia. Especially, the uses of RHS in residential development as a must for future in reducing the uses of treated water supply. Hence, the findings provide additional knowledge on the implementing RHS in Malaysia